Off-Label and Off-NCCN Guidelines Uses of Antineoplastic Drugs in China - Weilan Wang; Man Zhu; Daihong Guo; Chao Chen; Dongxiao Wang; Fei Pei; Liang Ma (Tehran University of Medical Sciences, 2013)
Background: To evaluate off-label and off-NCCN guidelines uses of antineoplastic drugs in a major Chinese hospital.Methods: Totally 1122 patients were selected from July to December 2011. Then, the off-label and off-NCCN guidelines uses of antineoplastic drugs were analyzed.Results: In 798 of 1122 patients (71.12%), drugs were used for off-label. In 317 of 1122 patients (28.25%), the drugs were prescribed for off-label and off-NCCN guidelines. 2591 medical orders for 1122 patients, 1051/2591 (40.56%) medical orders were off-label; 445/2591(17.17%) medical orders were off-label and off-NCCN guidelines. In 445 off-label and off-NCCN medical orders, 399 (89.66%) were unapproved indications, 38 (8.54%) were unapproved drug concentration and 12 (2.70%) were unapproved route of administration. Percentage of off-label and off-NCCN guidelines drug uses in male was higher than that in female (21.92% vs. 11.39%, P<0.01). Compared with other lines of treatment, percentage of off-label and off-NCCN guidelines drug uses in postoperative adjuvant was the smallest (P<0.01) and percentage in three or multi-line treatments was the highest (P<0.01). The pancreatic cancer possessed the highest percentage (38.74%) of off-label and off-NCCN guidelines drug uses among all types of cancer (P<0.01).Conclusion: Off-label uses of antineoplastic drugs are generally common in China hospitals based on NCCN guidelines. The fact suggests that anti-tumor treatment was relatively standard in China. Off-label and off-NCCN guidelines drug uses were mainly for individual treatment. Doctors should fully consider the adverse drug reaction, contraindication, cautions and increase the drug security monitoring. Uncorrected drug concentration should be avoided for drug risk